The Transformation of the Dilemma of Role Exchange in the Household: Analyzed Gender in Family Resilience Discourse in National Law and Islamic Law - Fatum Abubakar; Mazroatus Saadah; Ulin Na'mah (IAIN Manado, 2023)
This article analyzes the dilemma of changing roles in a household that is often unequal. Inequality occurs due to the wife's dominant role in meeting the family's needs; the wife bears a double burden compared to the husband. This study uses qualitative research with a literature research system through a formal juridical approach and gender analysis. The subject of this research refers to the articles in the Marriage Act and Compilation of Islamic Law. Researchers chose purposive sampling based on specific criteria and categories that can be described and analyzed. The findings of this study indicate the dilemma of relationships and roles in the household, where the ideal relationship within the family must be a provision for family resilience to realize national resilience. In addition, working women must be able to carry out their rights and obligations in a balanced way, even though information technology and the media are challenges to family life today. The optimization of the marriage guidance program and the reconstruction of Islamic Family Law and the Marriage Law must serve as an affirmation basis for the dynamics of marital relationship patterns. However, society must also understand that the social role of a partner is not absolute. His position can be exchanged as needed for the continuation of the marriage.